A review on plant-microbial interactions, functions, mechanisms and emerging trends in bioretention system to improve multi-contaminated stormwater treatment. (15th September 2021) - Mehmood, Tariq; Gaurav, Gajendra Kumar; Cheng, Liu; Klemeš, Jiří Jaromír; Usman, Muhammad; Bokhari, Awais; Lu, Jie
Abstract: Management and treatment of multi-polluted stormwater in bioretention system have gained significant attraction recently. Besides nutrients, recent source appointment studies found elevated levels of Potentially toxic metal(loid)s (PTMs) and contaminants of emerging concern (CECs) in stormwater that highlighted many limitations in conventional media adsorption-based pollutant removal bioretention strategies. The substantial new studies include biological treatment approaches to strengthen pollutants degradation and adsorption capacity of bioretention. The knowledge on characteristics of plants and their corresponding mechanisms in various functions, e.g., rainwater interception, retention, infiltration, media clogging prevention, evapotranspiration and phytoremediation, is scattered. The microorganisms' role in facilitating vegetation and media, plant-microorganism interactions and relative performance over different functions in bioretention is still unreviewed. To uncover the underneath, it was summarised plant and microbial studies and their functionality in hydrogeochemical cycles in the bioretention system in this review, contributing to finding their interconnections and developing a more efficient bioretention system. Additionally, source characteristics of stormwater and fate of associated pollutants in the environment, the potential of genetical engineered plants, algae and fungi in bioretention system as well as performance assessment of plants and microorganisms in non-bioretention studies to propose the possible solution of un-addressed problems in bioretention system have been put forward in this review. The present review can be used as an imperative reference to enlighten the advantages of adopting multidisciplinary approaches for the environment sustainability and pollution control. Graphical abstract: Image 1 Highlights: The fate of point and nonpoint stormwater pollution source evaluated. Plants regulated hydrology and pollutant treatment in the bioretention system. The plant's architectural traits as their main selection criteria were justified. Plant-microbes interaction effectively treated multi-polluted stormwater. Symbiosis and genetically engineered plants studies are warranted in bioretention.